Postbiotics From Lactobacillus Johnsonii Activates Gut Innate Immunity to Mitigate Alcohol‐Associated Liver Disease - Ruopeng Yin; Tao Wang; Jingzu Sun; Huanqin Dai; Yuting Zhang; Ningning Liu; Hongwei Liu (Advanced Science)
Abstract Prolonged alcohol consumption disrupts the gut microbiota and the immune system, contributing to the pathogenesis of alcohol‐associated liver disease (ALD). Probiotic‐postbiotic intervention strategies can effectively relieve ALD by maintaining gut homeostasis. Herein, the efficacy of heat‐killed Lactobacillus johnsonii (HKLJ) in mitigating alcoholic liver damage is demonstrated in mouse models of ALD. The gut‐liver axis is identified as a pivotal pathway for the protective effects of L. johnsonii against ALD. Specifically, HKLJ is found to upregulate the expression of intestinal lysozymes, thereby enhancing the production of immunoregulatory substances from gut bacteria, which subsequently activated the Nucleotide‐binding oligomerization domain 2 (NOD2)‐interleukin (IL‐23)‐IL‐22 innate immune axis. The elevated IL‐22 upregulated the antimicrobial peptide synthesis to maintain intestinal homeostasis and moreover activated the Signal transducer and activator of Transcription3 (STAT3) pathway in the liver to facilitate the repair of hepatic injuries. The heat‐killed L. johnsonii provoked immunity helps correct the gut microbiota dysbiosis, specifically by reversing the reduction of butyrate‐producing bacteria (such as Faecalibaculum rodentium) and the expansion of opportunistic pathogens (such as Helicobacter sp. and Pichia kudriavzevii) induced by ethanol. The findings provide novel insights into the gut microbiota‐liver axis that may be leveraged to enhance the treatment of ALD.